Cell States in Cancer: Drivers, Passengers, and Trailers - Gargiulo, Gaetano; Serresi, Michela; Marine, Jean-Christophe (Cancer discovery, 2024)
Cancer is traditionally perceived through a genetic lens, with therapeutic strategies targeting oncogenic driver mutations. We advocate an overarching framework recognizing tumors as comprising driver, passenger, and trailer cell states: Tailoring therapies to simultaneously target driver genetics and cell states may enhance effectiveness and durability. We redefine cancer progression by introducing a model that categorizes tumor cells into "driver," "passenger," and "trailer" phenotypes, expanding the focus on genetic aberrations to cellular behavior. This approach offers a roadmap to guide refining therapeutic strategies for more precise and durable cancer treatments that address tumor heterogeneity and plasticity.